2015
DOI: 10.1002/ajmg.a.36922
|View full text |Cite
|
Sign up to set email alerts
|

A study of the clinical and radiological features in a cohort of 93 patients with a COL2A1 mutation causing spondyloepiphyseal dysplasia congenita or a related phenotype

Abstract: Type 2 collagen disorders encompass a diverse group of skeletal dysplasias that are commonly associated with orthopedic, ocular, and hearing problems. However, the frequency of many clinical features has never been determined. We retrospectively investigated the clinical, radiological, and genotypic data in a group of 93 patients with molecularly confirmed SEDC or a related disorder. The majority of the patients (80/93) had short stature, with radiological features of SEDC (n = 64), others having SEMD (n = 5),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 32 publications
(42 reference statements)
7
73
1
Order By: Relevance
“…For example, Silveira et al reported clinical and radiological follow-up of six unrelated patients with a R989C mutation that was associated with a severe SEDC phenotype, which was consistent with the phenotypes of twelve other R989C mutation cases [18]. In contrast, three patients with a G504S mutation showed mild SEDC, SEDT, and severe SEDC phenotypes [8, 15]. Likewise, a G513S mutation in a 4-year-old was associated with mild SEDC, but was also associated with a lethal form of SEDC that resulted in neonatal death [15, 19].…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…For example, Silveira et al reported clinical and radiological follow-up of six unrelated patients with a R989C mutation that was associated with a severe SEDC phenotype, which was consistent with the phenotypes of twelve other R989C mutation cases [18]. In contrast, three patients with a G504S mutation showed mild SEDC, SEDT, and severe SEDC phenotypes [8, 15]. Likewise, a G513S mutation in a 4-year-old was associated with mild SEDC, but was also associated with a lethal form of SEDC that resulted in neonatal death [15, 19].…”
Section: Discussionmentioning
confidence: 66%
“…Recurrent COL2A1 mutations have been reported in several studies; some mutations displayed similar phenotypes, while others displayed distinct phenotypes [8, 1520]. For example, Silveira et al reported clinical and radiological follow-up of six unrelated patients with a R989C mutation that was associated with a severe SEDC phenotype, which was consistent with the phenotypes of twelve other R989C mutation cases [18].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Therefore, mutations in genes that encode matrix collagens, proteoglycans, non-collagenous proteins and their processing enzymes affect growth plate chondrogenesis by several mechanisms and causes growth failure with a wide phenotypic spectrum (Table 1). For example, mutations in collagens [101108], fibrillin 1 [109], cartilage oligomeric matrix protein [110111], matrillin-3 [112], aggrecan [113114] and perlecan [115] have been reported to cause short stature of variable severity. Mutations in genes encoding extracellular matrix proteins may also affect connective tissue beyond the growth plate, causing various degrees of skeletal and joint problems, as well as some conditions with low bone mineral density (Table 1).…”
Section: Genetics Of Short Staturementioning
confidence: 99%
“…24 Our observations provide a nearly 15% increase in the number of novel variants shown in previous records and illustrate the wide mutability of the COL2A1 gene and its various associated phenotypes. 25 Our results also demonstrate the limits of focusing on a single gene during genetic diagnosis given the lack of clear phenotype to genotype correlations. To address this issue, we are now implementing next-generation sequencing approaches in our routine settings.…”
Section: Discussionmentioning
confidence: 73%